2018
DOI: 10.3390/ijerph15030445
|View full text |Cite
|
Sign up to set email alerts
|

Urban Green Space and Its Impact on Human Health

Abstract: Background: Over half of the world’s population now lives in urban areas, and this proportion is expected to increase. While there have been numerous reviews of empirical studies on the link between nature and human health, very few have focused on the urban context, and most have examined almost exclusively cross-sectional research. This review is a first step toward assessing the possibility of causal relationships between nature and health in urban settings. Methods: Through systematic review of published l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
557
2
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 819 publications
(604 citation statements)
references
References 99 publications
(369 reference statements)
27
557
2
18
Order By: Relevance
“…Although, evidence on associations between NCD risk factors and urban characteristics are inconsistent (Canterbury District Health Board, 2016;Kondo et al, 2018), neighborhood with greater green space, walkability, access to resources and amenities, residential density, environmental quality and aesthetics, and low air and noise pollution has been found to decrease the NCD risk (Canterbury District Health Board, 2016). The growth of roads without footpath and trees and lack of UGS in South Asian cities impede the walkability and thus the potential opportunity for physical activities (Asian Development Ban, 2011; Shanahan et al, 2016;Kondo et al, 2018). With increasing purchasing power, cars stand more as symbols of high socioeconomic status than a mere means of transportation (Senbil et al, 2007).…”
Section: Cvds and Green Space Linkagementioning
confidence: 99%
“…Although, evidence on associations between NCD risk factors and urban characteristics are inconsistent (Canterbury District Health Board, 2016;Kondo et al, 2018), neighborhood with greater green space, walkability, access to resources and amenities, residential density, environmental quality and aesthetics, and low air and noise pollution has been found to decrease the NCD risk (Canterbury District Health Board, 2016). The growth of roads without footpath and trees and lack of UGS in South Asian cities impede the walkability and thus the potential opportunity for physical activities (Asian Development Ban, 2011; Shanahan et al, 2016;Kondo et al, 2018). With increasing purchasing power, cars stand more as symbols of high socioeconomic status than a mere means of transportation (Senbil et al, 2007).…”
Section: Cvds and Green Space Linkagementioning
confidence: 99%
“…In the last 20 years the research on health determinant factors clearly shifted the attention to the social dimension of the individual's life (Badland and Pearce, 2019;Byrne et al, 2014;Carmichael, 2019;Corburn, 2004;House et al, 2007;Jackson L, 2003;Konstantinos Tzoulasa et al, 2007;Lee AC. Maheswaran R. and Lee A.C.K., 2011;Leeuw, 1999;M.C. et al, 2018;Schram-Bijkerk et al, 2018).…”
Section: The Research Themesmentioning
confidence: 99%
“…For decades, empirical evidence has found that the interaction with green space using objective measures is associated with better physical health [1,2], physical activity [3][4][5][6][7][8], mental health [9][10][11][12][13][14][15], stress [16,17], and self-reported and self-rated health [18][19][20][21][22]. There is also growing evidence indicating that perceived greenness also contributes to health [23].…”
Section: Introductionmentioning
confidence: 99%